Immunomodulation for the Treatment of Chronic Chagas Disease Cardiomyopathy: A New Approach to an Old Enemy - Santos, Emanuelle de Souza; Silva, Dahara Keyse Carvalho; Reis, Bruna Padilha Zurita Claro dos; Barreto, Breno Cardim; Cardoso, Carine Machado Azevedo; Ribeiro dos Santos, Ricardo; Meira, Cássio Santana; Soares, Milena Botelho Pereira (Frontiers in Cellular and Infection Microbiology, 2021)
Chagas disease is a parasitic infection caused by the intracellular protozoan Trypanosoma cruzi. Chronic Chagas cardiomyopathy (CCC) is the most severe manifestation of the disease, developed by approximately 20-40% of patients and characterized by occurrence of arrhythmias, heart failure and death. Despite having more than 100 years of discovery, Chagas disease remains without an effective treatment, especially for patients with CCC. Since the pathogenesis of CCC depends on a parasite-driven systemic inflammatory profile that leads to cardiac tissue damage, the use of immunomodulators has become a rational alternative for the treatment of CCC. In this context, different classes of drugs, cell therapies with dendritic cells or stem cells and gene therapy have shown potential to modulate systemic inflammation and myocarditis in CCC models. Based on that, the present review provides an overview of current reports regarding the use of immunomodulatory agents in treatment of CCC, bringing the challenges and future directions in this field.